O85 Durable responses in anti-PD-1 refractory melanoma following intratumoral injection of a toll-like receptor 9 (TLR9) agonist, CMP-001, in combination with pembrolizumab. (15th April 2020) - Milhem, Mohammed; Zakharia, Yousef; Davar, Diwakar; Buchbinder, Elizabeth; Medina, Theresa; Daud, Adil; Ribas, Antoni; Niu, Jiaxin; Gibney, Geoffrey; Margolin, Kim; Olszanski, Anthony; Mehmi, Interjit; et al.
Abstract : Background: Intratumoral (IT) injection of CMP-001, a CpG-A TLR9 agonist packaged within a virus-like particle, is designed to activate tumor-associated plasmacytoid dendritic cells, inducing an interferon-rich tumor microenvironment and anti-tumor CD8+ T cell responses. Methods: CMP-001-001 is an ongoing Phase 1b trial evaluating the safety and efficacy of CMP-001 in combination with pembrolizumab (Part 1; N = 144) or alone (Part 2; N = 23) in patients with advanced melanoma resistant to prior anti-PD-1 therapy (Tables 1). CMP-001 is administered IT into accessible lesion(s) either with, or without on-site saline dilution (table 1 ), and response assessed by RECIST v1.1. Monotherapy patients who progress can be rolled over onto combination therapy and continue on study. Baseline and on-therapy serum is analyzed for cytokines, and immunohistochemistry and RNA-Seq are performed on available tumor biopsies. Results: Adverse events (AEs) attributed to CMP-001 in combination with pembrolizumab or as monotherapy consisted predominately of transient low-Grade flu-like symptoms and injection site reactions: Grade 3+ related AEs were reported in 33% of patients treated with combination therapy and 22% of patients with monotherapy. The Objective Response Rate (ORR) with undiluted CMP-001 in combination with pembrolizumab was 24% (18/75; 95% confidence interval: 15%-35% (table 1 ); on-site dilution of CMP-001 was associated with a substantial decrease in ORR to 12% (7/61; 95% confidence interval: 5%-22% (table 1 ). Three additional patients had a delayed partial response after an initial period of disease progression. Anti-tumor response was comparable between injected and uninjected lesions. The median duration of response to combination therapy has not been reached. The ORR to CMP-001 monotherapy was 22% (5/23; 95% confidence interval: 7%-44% (table 1 ); time from last anti-PD-1 therapy before CMP-001 was 1.5 to >20 months in responders; 3 of the patients responding to CMP-001 monotherapy achieved PR at the first evaluation, but progressed by the second evaluation. Serum and tumor biopsy translational studies in the patients receiving combination therapy supported the proposed mechanism of TLR9 activation and identified a possible association between induction of serum CXCL10 and response. Conclusions: IT CMP-001 alone and in combination with pembrolizumab appears well tolerated, can reverse resistance to anti-PD-1 therapy, and can produce deep and durable clinical responses in patients with advanced melanoma. Ethics Approval: CMP-001-001 was centrally approved by the WCG-WIRB, WIRB approval tracking number 20152597.